2022
DOI: 10.1101/2022.09.26.22280374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic correlations between gut microbiota genera and Alzheimer’s Disease

Abstract: Background: A growing body of evidence suggests that dysbiosis of the human gut microbiota is associated with neurodegenerative diseases like Alzheimers disease (AD) via neuroinflammatory processes across the microbiota-gut-brain axis (MGBA). The gut microbiota affects brain health through the secretion of toxins and short-chain fatty acids, which modulates gut permeability and numerous immune functions. Observational studies indicate that AD patients have reduced microbiome diversity, which could contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…We also found that genetic prediction of genus Eisenbergiella was associated with a decreased risk of Long COVID. Eisenbergiella has been identified as harboring species capable of metabolizing the SCFA butyrate derived from dietary carbohydrates (Amir et al, 2014;Togo et al, 2016;Cammann et al, 2023). Butyrate, a prominent SCFA metabolite in the colon, has been suggested as a key mediator in the inflammatory response within the colon.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that genetic prediction of genus Eisenbergiella was associated with a decreased risk of Long COVID. Eisenbergiella has been identified as harboring species capable of metabolizing the SCFA butyrate derived from dietary carbohydrates (Amir et al, 2014;Togo et al, 2016;Cammann et al, 2023). Butyrate, a prominent SCFA metabolite in the colon, has been suggested as a key mediator in the inflammatory response within the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified that five bacterial taxa including family Victivallaceae, genus Eubacterium fissicatena group, genus Escherichia Shigella, genus Peptococcus and genus Sellimonas reduce the risk of endocarditis, and previous studies support our findings to some extent. Genus Eubacterium fissicatena group produces butyrate, which not only maintains normal intestinal permeability, but also exerts antiinflammatory effects (Cammann et al, 2023). Genus Peptococcus plays an important role in antioxidant and maintenance of normal intestinal morphology (Zhang L. et al, 2021;Zhu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These microbes facilitate optimal brain health and function by modulating the integrity of intestinal and brain barriers and regulating homeostasis within the metabolic, immune, endocrine, and nervous systems (Chok et al, 2021). An imbalance of microbial diversity, or dysbiosis, can affect brain health via the microbiota-gut-brain axis (MGBA) through the secretion of toxins, cytokines, and short-chain fatty acids which in turn, affect gut permeability, immune response, and blood brain barrier integrity (Cammann et al, 2023). Growing evidence indicates that bacteria in the gut can release lipopolysaccharide (LPS) and amyloids that trigger microglial activation in the brain, which promote upregulation of proinflammatory cytokines and the culmination of neuroinflammation related to AD pathogenesis (Cammann et al, 2023).…”
Section: Gender Considerations Of the Microbiomementioning
confidence: 99%
“…An imbalance of microbial diversity, or dysbiosis, can affect brain health via the microbiota-gut-brain axis (MGBA) through the secretion of toxins, cytokines, and short-chain fatty acids which in turn, affect gut permeability, immune response, and blood brain barrier integrity (Cammann et al, 2023). Growing evidence indicates that bacteria in the gut can release lipopolysaccharide (LPS) and amyloids that trigger microglial activation in the brain, which promote upregulation of proinflammatory cytokines and the culmination of neuroinflammation related to AD pathogenesis (Cammann et al, 2023). Due to the bidirectional nature of the MGBA, directly via the vagus nerve and indirectly via metabolites, inflammation in the periphery can translate to the CNS and contrarywise (Jamar et al, 2021).…”
Section: Gender Considerations Of the Microbiomementioning
confidence: 99%